Pengaruh Adopsi Pembayaran Digital (QRIS/E-Wallet) Terhadap Perbaikan Arus Kas UMKM dengan Literasi Keuangan Sebagai Variabel Moderasi - Wulan, Titis Sri; Reni; Nurvianti, Elmi; Putra, Feby Arma (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of digital payment adoption through the use of QRIS and e-wallets on improving cash flow for MSMEs in Indonesia, and to examine the role of financial literacy as a moderating variable. The study used a quantitative approach with a survey method of MSMEs that have implemented digital payments in their business activities. Data were collected through a structured questionnaire using a Likert scale and analyzed using path analysis to test the direct effect between variables, as well as moderation tests through the formation of interaction variables. The results show that digital payment adoption has a positive effect on improving MSME cash flow. Financial literacy also has a positive effect on the quality of cash flow management. Furthermore, financial literacy has been shown to strengthen the influence of digital payment adoption on improving cash flow, so that the benefits of QRIS and e-wallet use are more optimal for MSMEs with higher levels of financial literacy. These findings emphasize that payment digitalization needs to be balanced with strengthening financial literacy. This study provides theoretical contributions to the study of MSME digital finance and practical implications for the formulation of integrated MSME policies and mentoring programs.